Professor Zbigniew Oszast – one of the most famous Cracow dermatologists - Jaworek, Andrzej; Jeliczko, Paulina; Sułkowska, Weronika; Pastuszczak, Maciej; Wojas-Pelc, Anna (Dermatology Review/Przegląd Dermatologiczny, 2013)
Zbigniew Oszast was born on 11th March 1903 in Lublin. His scientific career started in 1929 and was constantly connected with the Department of Dermatology Jagiellonian University in Krakow. For many years professor Oszast was especially interested in radiotherapy of skin diseases. He was educated in many prestigious European institutions – among others: Finsen Institute, Electropathology Institute under professor Jelinek's supervision, Sauerbruch’s and Hermansdorfer’s Clinic. Extensive experience was very helpful to create a radiotherapy ward which was part of the Dermatology Department. During World War II it was the greatest radiotherapy institution in Poland. Prof Oszast was also involved in research on: ultrashort waves treatment of skin diseases, coagulation of skin lesions, therapy of skin tuberculosis and radiotherapy of skin cancers connected to tuberculosis luposa. He was also involved in development of physical therapy in Poland. Throughout the period of World War II prof Oszast was fully responsible for the Dermatology Department as well as the dermatology and radiotherapy ward in Saint Lazarus Hospital. He was a person with a versatile mind – a great scientist, excellent teacher and talented organiser. Besides research work he wrote numerous biographical articles about many famous physicians. Zbigniew Oszast died on 10th November 1967 in Krakow.